The Scaly-foot Snail genome and implications for the origins of biomineralised armour - Jin Sun (Nature Portfolio, 2020)
The Scaly-foot Snail, Chrysomallon squamiferum, is a model for understanding the evolution of biomineralised armour. Here, the authors present a chromosome-level reference genome assembly and tissue-specific transcriptomic data for this enigmatic organism.